Effect of disodium monofluorphosphate on plasma and blood viscosity in the rat (2008)
Alpha macroglobulins (AM) are plasma proteins whose main function is to inactivate proteinases, protecting the tissues from the action of these enzymes. AM have influence on plasma viscosity (PV) and binds monofluorophosphate (MFP), which disturbs its homeostasis. The aim of this work was to evaluate whether the administration with MFP could modify blood viscosity. AM levels (?mol/l), PV (mPa·s), viscosity of red blood cells suspensions in NaCl 9 g/l (VES) and in autologue plasma (VEP) were measured in fifty-day old rats after a single dose of 80 ?mol MFP or after 30 days of treatment with 80 ?mol of MFP. Relative viscosity (RV) was calculated as the ratio VEP/PV. AM and PV increased significantly after 30 min of an oral dose of MFP. Controls (n=6), AM: 19.65±0.85, PV: 1.39±0.01, treated (n=6), AM: 22.88±0.75 (p less than 0.05), PV: 1.76±0.14 (p less than 0.05). After 30 days of treatment with MFP, AM and PV increased significantly. Controls (n=6), AM: 10.76±1.33, PV: 1.19±0.04, treated (n=6), AM: 17.66±1.27 (p less than 0.05), PV: 1.38±0.03 (p less than 0.05). The treatment with MFP modifies neither the VEP nor the RV. These results would indicate that AM and/or MFP did not interact with erythrocyte membrane and did not modify erythrocyte deformability. © 2008 - IOS Press and the authors. All rights reserved.